2017
DOI: 10.1080/00016357.2017.1392602
|View full text |Cite
|
Sign up to set email alerts
|

Selective versus non-selective removal for dental caries: a systematic review and meta-analysis

Abstract: The efficacy of selective caries removal appears comparable to that of non-selective caries removal in children, with similar pulpal symptoms and failure, but selective caries removal may result in a low incidence of pulpal exposure. However, larger-scale RCTs with long-term follow-up are required to confirm this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 22 publications
4
33
0
5
Order By: Relevance
“…Recent systematic reviews demonstrated that the risk of pulpal exposure is higher with CCP compared with SCR in primary teeth and that pulpo-periodontal complications do not significantly differ between these two caries removal strategies. 6,8,23,24 Finally, restoration longevity in primary teeth appears to be longer following CCR than SCR. 8,25 Only 35% of the respondents indicated SCR; this could be explained by the lack of consensus and the contradictory results found in the literature; moreover, this may be linked to the fact that a large proportion (57%) of the respondents were academics practicing in university hospitals (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Recent systematic reviews demonstrated that the risk of pulpal exposure is higher with CCP compared with SCR in primary teeth and that pulpo-periodontal complications do not significantly differ between these two caries removal strategies. 6,8,23,24 Finally, restoration longevity in primary teeth appears to be longer following CCR than SCR. 8,25 Only 35% of the respondents indicated SCR; this could be explained by the lack of consensus and the contradictory results found in the literature; moreover, this may be linked to the fact that a large proportion (57%) of the respondents were academics practicing in university hospitals (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Once practice restrictions begin to be eased, continued management of dental disease with contemporary dentistry through minimally interventive concepts and other non‐AGPs, whilst viral transmission risk remains high, will be pertinent. These include atraumatic restorative treatment (ART), 70 sealing in carious lesions using fissure sealants, 71 silver diamine fluoride, 72 selective caries removal, 73 and the Hall Technique 74 . The importance of toothbrushing with fluoridated toothpaste to prevent tooth decay developing should continue to be emphasised during contact with patients, and there are opportunities being taken for dentists to carry out telephone and video consultations with parents to promote positive oral health behaviours.…”
Section: Covid‐19mentioning
confidence: 99%
“…An additional study by Anaute-Netto et al 395 investigated the effect of resin infiltration over a longer period of 3 years. The infiltrant was effective in preventing caries progression in noncavitated pit and fissures after 3 years of clinical evaluation compared with the conventional sealants.…”
Section: Sealing and Infiltration Of Cariesmentioning
confidence: 99%
“…However, larger-scale RCTs with long-term follow-up are required to confirm this conclusion. 395 If carious tissue can be left untouched and sealed with a restorative material, it means that a great change in the understanding of the disease has occurred in these past few years. An elegant review by Professor Schwendicke 396 summarizes all these changes to provide clinical recommendations for the readers.…”
Section: Sealing and Infiltration Of Cariesmentioning
confidence: 99%